2021
DOI: 10.1161/circresaha.121.319060
|View full text |Cite
|
Sign up to set email alerts
|

An Immuno-Cardiac Model for Macrophage-Mediated Inflammation in COVID-19 Hearts

Abstract: Rationale: While respiratory failure is a frequent and clinically significant outcome of COVID-19, cardiac complications are a common feature in hospitalized COVID-19 patients and are associated with worse patient outcomes. The cause of cardiac injury in COVID-19 patients is not yet known. Case reports of COVID-19 autopsy heart samples have demonstrated abnormal inflammatory infiltration of macrophages in heart tissues. Objective: Generate an immuno-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 52 publications
(71 reference statements)
1
52
0
Order By: Relevance
“…In keeping with this, high genotype-inferred pulmonary expression of the monocyte–macrophage chemotactic receptor CCR2 is associated with severe disease, and numerous monocyte/macrophage chemotactic factors are elevated in blood, bronchoalveolar lavage fluid and whole lung tissue in COVID-19 [ 4 , 9 , 10 ]. These expanded macrophage populations are highly activated and with aberrant expression of key inflammation-associated molecules, often alongside expression of genes associated with tissue repair and fibrogenesis [ 2 , 11 , 12 ]. Interestingly, while epithelial cells are clearly the main viral target of SARS-CoV-2 infection, studies have reported viral S protein within macrophages [ 1 , 3 ].…”
Section: Pulmonary Immunopathology Drives Disease Severity In Covid-19mentioning
confidence: 99%
“…In keeping with this, high genotype-inferred pulmonary expression of the monocyte–macrophage chemotactic receptor CCR2 is associated with severe disease, and numerous monocyte/macrophage chemotactic factors are elevated in blood, bronchoalveolar lavage fluid and whole lung tissue in COVID-19 [ 4 , 9 , 10 ]. These expanded macrophage populations are highly activated and with aberrant expression of key inflammation-associated molecules, often alongside expression of genes associated with tissue repair and fibrogenesis [ 2 , 11 , 12 ]. Interestingly, while epithelial cells are clearly the main viral target of SARS-CoV-2 infection, studies have reported viral S protein within macrophages [ 1 , 3 ].…”
Section: Pulmonary Immunopathology Drives Disease Severity In Covid-19mentioning
confidence: 99%
“…To establish system level relevance of IL-1 β treated hCOs for modeling COVID-19 hearts, we performed RNA sequencing (RNAseq) on hCOs with/without IL-1 β treatment and compared their transcriptomic profiles to COVID-19 and healthy heart autopsy samples from publicly available datasets 38 . We first plotted the top differentially expressed genes (DEGs) for our IL-1β treated hCOs (compared to control hCOs) and the COVID-19 hearts (compared to healthy controls).…”
Section: Resultsmentioning
confidence: 99%
“…The R package, DESeq2 (v1.24.0) [doi: 10.1186/s13059-014-0550-8], was used to perform the differential gene expression analysis. Human in vivo myocardium samples containing healthy myocardium (n = 5) and myocardium from COVID infected patients 38 (n = 3) were retrieved on the National Institute of Health's Gene Expression Omnibus (GEO), GSE169241. Differential gene expression analysis was performed using Rstudio (v1.3.1093) (R language v3.6.1).…”
Section: Fabrication Of Organoidsmentioning
confidence: 99%
“…1 ). The main target cells for SARS-CoV-2 infection are ACE2-positive cells, such as type II alveolar epithelial (AT2) cells and resident alveolar macrophages in the lung, and the endothelial cells in the liver, kidney, hearts and intestines [ 16 20 ].
Fig.
…”
Section: Overview Of Sars-cov-2 Infection (Covid-19)mentioning
confidence: 99%